Transformasi Digital dalam Manajemen Pemasaran Analisis Literatur tentang Penggunaan TIK - Pamungkas, Ibrahim Bali; Tajuddien, Rahadyan; Praditya, Alvin (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Digital transformation is essential for companies to remain competitive in today’s dynamic market. Through the use of Information and Communication Technology (ICT), businesses can enhance marketing management by automating processes, utilizing data analytics, and creating digital customer experiences. This study adopts a literature review method to explore how digital transformation impacts marketing practices. A total of 45 national journal articles from 2019 to 2024 were collected from garuda.kemdikbud.go.id and analyzed. The findings reveal key trends: many studies focus on digital marketing innovation, e-commerce, and data mining. Training programs and skill development are frequently highlighted, especially for empowering SMEs and youth communities. Goals such as customer loyalty and entrepreneurial development are common. In terms of methods, qualitative approaches, technology-based analytics, and community interventions like training and focus groups are widely applied. Target populations often include SMEs, young entrepreneurs, and specific customer segments. Despite its benefits, digital transformation poses challenges such as high implementation costs, limited digital skills, and data security risks. To address these issues, strategies including human capital investment, strategic partnerships, and proactive data security measures are recommended. In conclusion, ICT-driven transformation can significantly boost marketing effectiveness and customer engagement. With proper planning and investment, companies can overcome barriers and achieve sustainable growth in the digital era.